The Algorithmic Guardian: The Role of Fitness Trackers in Preventive Healthcare - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
Meta Description: Explore how fitness trackers, powered by AI and machine learning, are revolutionizing preventive healthcare by transforming passive data in...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Machine Learning; Wearable Technology